Effect of ANGPTL7 on Proliferation and Differentiation of MC3T3-E1 Cells - Lu, XiaoQing (Med Sci Monit, 2019)
BACKGROUND: Angiopoietin-like proteins (ANGPTL) are a family of secretory glycoproteins that are involved in many pathophysiological processes. ANGPTL7 is a newly-discovered member of the ANGPTL family and plays a role in corneal morphogenesis, angiogenesis, glaucoma, and cancer. To date, whether ANGPTL7 is involved in osteoporosis is unknown. Therefore, to discover the effects of ANGPTL7 on osteoporosis, we explored the expression of ANGPTL7 in preosteoblasts and assessed the mechanism underlying its effects on proliferation and differentiation abilities of preosteoblasts. MATERIAL/METHODS: Mouse MC3T3-E1 cells were cultured in osteogenic medium for osteogenic differentiation. The expression levels of ANGPTL7 were detected by RT-qPCR and Western blot assays. Moreover, the overexpressed plasmid of ANGPTL7 pMSCV-ANGPTL7 was transfected into MC3T3-E1 cells. CCK-8 was used to evaluate cell proliferation. ALP activity detection and alizarin red staining were performed to measure the effect of ANGPTL7 on osteogenic differentiation. The expression levels bone morphogenetic proteins (BMPs) and osteogenic markers ALP, runt-related transcription factor 2 (Runx2), osteocalcin (OCN), and collagen I (Col I) were analyzed by Western blot. RESULTS: When MC3T3-E1 cells were exposed to osteogenic medium, there was a significant increase in ANGPTL7, and overexpression of ANGPTL7 markedly promoted cell proliferation, ALP activity, and mineralization. Moreover, ANGPTL7 upregulated the levels of BMPs, especially BMP2/7, and the osteogenic markers ALP, Runx2, OCN, and Col I. CONCLUSIONS: The results suggest that by regulating the expression of BMPs, ANGPTL7 directly promotes proliferation, differentiation, and mineralization of osteoblasts.